2021
DOI: 10.1101/2021.01.12.20248588
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacterial superinfection pneumonia in SARS-CoV-2 respiratory failure

Abstract: BackgroundSevere community-acquired pneumonia secondary to SARS-CoV-2 is a leading cause of death. Current guidelines recommend patients with SARS-CoV-2 pneumonia receive empirical antibiotic therapy for suspected bacterial superinfection, but little evidence supports these recommendations.MethodsWe obtained bronchoscopic bronchoalveolar lavage (BAL) samples from patients with SARS-CoV-2 pneumonia requiring mechanical ventilation. We analyzed BAL samples with multiplex PCR and quantitative culture to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Studies in which peripheral blood is serially sampled generally show resolution of these abnormalities over the course of the disease. However, it is important to note that high rates of ventilatorassociated pneumonia in patients with SARS-CoV-2 pneumonia (44% in our cohort) may confound these results (70).…”
Section: Similarities In Pneumonia Secondary To Sars-cov-2 Versus Other Respiratory Pathogensmentioning
confidence: 86%
See 1 more Smart Citation
“…Studies in which peripheral blood is serially sampled generally show resolution of these abnormalities over the course of the disease. However, it is important to note that high rates of ventilatorassociated pneumonia in patients with SARS-CoV-2 pneumonia (44% in our cohort) may confound these results (70).…”
Section: Similarities In Pneumonia Secondary To Sars-cov-2 Versus Other Respiratory Pathogensmentioning
confidence: 86%
“…In anticipation of the pandemic, we modified our bronchoscopy protocols to ensure operator safety. Our clinical teams performed bronchoscopies in patients with SARS-CoV-2 pneumonia, as clinically indicated, and used analysis of BAL fluid with quantitative bacterial cultures, multiplex PCR, and fungal antigens to guide antimicrobial therapy (28,70). We compared BAL fluid samples from patients with SARS-CoV-2 pneumonia with serial BAL fluid samples we collected from 211 patients with severe pneumonia secondary to other pathogens requiring mechanical ventilation before the pandemic.…”
Section: Studies Of Sars-cov-2 Pneumonia In Patientsmentioning
confidence: 99%
“…First, the circulating RAS may not reflect the local tissue levels, which may be particularly altered in the lungs in COVID-19 ( 17 ). An assessment of the lung compartment in COVID-19 is more challenging, though others have shown that bronchoalveolar lavage in patients with COVID-19 is feasible ( 18 ). Second, our study is likely underpowered to reveal true differences in circulating RAS components.…”
Section: Discussionmentioning
confidence: 99%
“…A thorough search into the literature (January 2020–June 2021) revealed many studies trying to address the AMR issue in the pandemic era. The main issues refer to patients with COVID-19 who may receive antimicrobial therapy (a) without a microbiological confirmation of the bacterial co-infection [ 18 , 31 , 32 , 33 , 34 , 35 , 36 ] and (b) often in the absence of a microbiological confirmation of the diagnosis [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. Lai et al [ 24 ] recorded the consumption of antibiotics in January–June 2019 vs. January–June 2020 in The National Taiwan University Hospital.…”
Section: Discussionmentioning
confidence: 99%